Discourse representation of dialogic principles in teacher-learner communication - Zarichna, Olena (Lesya Ukrainka Eastern European National University, 2016)
This article presents a consideration of the problem of discourse representation of pedagogic dialogue in teacher-learner interactions. The functional parameters inherent in the pedagogical process condition an understanding of pedagogic dialogue as a personality-centered type of communication based on the principles of value oriented treatment, alterocentrism, personal inclusion, metaposition of the teacher, personal authenticity and thereby distinguished from the liberal and democratic paradigm. As a special challenge for this study there has been elaborated a scheme of dialogic discourse specified in corresponding discourse patterns, markers and speech acts. The focus is made on those discourse elements featuring the principles of pedagogic dialogue. In the course of inclusive observation conducted on the basis of this scheme there were determined three basic communication styles featuring different levels of communicative disposition: dialogic, semi-dialogic and monologic. The statistics reveal comparatively low percentage of young teachers possessing dialogic dispositions and strategies in pedagogic communication which calls for certain alterations in the system of teacher training as well as personality development of future educators. У статті розглянуто проблему дискурсивної репрезентації педагогічного діалогу у взаємодії учителі й учнів.Функціональні параметри педагогічного процесу зумовлюють розуміння педагогічного діалогу як особистісно-зорієнтованого типу спілкування, що ґрунтується на принципах ціннісного ставлення, домінанти на Іншому, особистісного включення, позиції позазнаходження і особистісної автентичності, що є альтернативним баченням відносно ліберально-демократичної концепції діалогу. У контексті даного дослідження було розроблено схему діалогічного дискурсу, специфіковану у відповідних дискурсивних патернах, маркерах і мовленнєвих актах. Особлива увага була приділена елементам дискурсу, які відображають принципи педагогічного діалогу. У ході включеного спостереження, проведеного у контексті цього дослідження, було визначено три основні комунікативні стилі, виражені у різних рівнях діалогічної диспозиції: діалогічний, напівдіалогічний і монологічний. Статистичні дані виявляють порівняно низький відсоток молодих учителів, які володіють діалогічною диспозицію і відповідними стратегіями педагогічного спілкування, що викликає потребу певних змін у системи професійної підготовки учителів, а також їхнього особистісного розвитку.
Keywords: dialogic discourse; teacher-learner communication; value oriented treatement; alterocentrism; discourse analysis; діалогічний дискурс; спілкування учителя і учнів; ціннісне ставлення; домінанта на Іншому; дискурс-аналіз